Towards More Effective Social Assistance in Russia : An Update of the System Performance Considering New National Target of Halving Poverty by 2024 - Yemtsov, Ruslan; Posarac, Aleksandra; Nagernyak, Maria; Albegova, Irina (World Bank, Washington, DC, 2019)
This report updates the assessment of the performance of the social protection (SP) system in Russia, using the 2014-2017 rounds of the Survey on Incomes and the Participation in Social Programs (VNDN in Russian) by the State Statistic Service of the Russian Federation (Rosstat), the largest household annual monitoring survey in Russia, and the main source of official data on poverty. The 2017 VNDN Survey round has a sample (about 150,000 households) that is 3 times larger than its standard sample size and it allows for a comprehensive assessment of the SP system performance both at the national and the regional levels. The context for the update is the 2018 May Decree by the President of Russia5, which defined the new strategic goals for socio-economic development and poverty alleviation in Russia. The Decree put human development and poverty reduction at the center of the Russia’s development strategy over the medium term. To achieve the May decree goals by 2024, the Government developed 12 National Projects, particularly in health, support to families and education, and allocated significant resources for their implementation. The national goals include halving poverty, increasing the quality of education and improving health status to extend longevity and economically active life. For social protection, the objectives pertain to higher efficiency and effectiveness, greater share of resources directed to families in need of assistance, better performance results and stronger alignment with human development goals. More recently, the Ministry of Labor and Social Protection launched a series of regional pilots to inform decisionmakers on good practice examples in implementing the reform in the regions. This update is intended to feed into this on-going process, enabling the World Bank team to continue to support the Government of the Russian Federation in its efforts to improve efficacy of its social assistance system. Through the RAS project, the social assistance team of the World Bank has established itself as credible source of robust analysis and solid technical advice.